Digital Marketing at SMES by Bibliometric Analisys - Syafri Naldi; Erna Maulina; Tetty Herawaty (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: Digital marketing has evolved from the marketing of products and services to digital channels for activities, institutions, and processes facilitated by digital technology. This study provides a disciplinary broad overview of the academic contribution to the marketing revolution by exploring changes in digital marketing research in SMEs cited by scientific researchers over 19 years (2001-2020). Thus, this paper presents a systematic literature review using bibliometric analysis with the aim of examining development trends, identifying gaps, understanding the advantages and benefits of digital marketing on SMEs and mapping out new hypotheses for future research. Design/methodology/approach: The method used is a bibliometric study to search for articles related to the research theme Findings: The results show that social media is the keyword that is often employed. Related research has been achieved in many countries, and the most predominant are England and America. Research limitations/implications: This study is limited to a single database, Scopus, from 2001 to 2020. Practical implications: The findings of this study are likely to serve as a starting point for future research in digital marketing.Besides, it becomes a resource to make the most of social media marketing to grow SMEs. Originality/value: This paper is original. Paper type: a Research Paper